2002
DOI: 10.1103/physreva.66.042310
|View full text |Cite
|
Sign up to set email alerts
|

Experimental realization of a continuous version of the Grover algorithm

Abstract: A continuous, analog version of the Grover algorithm is realized using NMR. The system studied is 23Na in a liquid crystal medium. The presence of quadrupolar coupling makes the spin I=3/2 nucleus a 2-qubit system. Applying a specially designed pulse sequence, the time evolution of the spin density operator is described in an interaction representation which has no external time-dependent radio-frequency fields. This approach is used to implement one instance of the continuous Grover search for the transform o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 23 publications
0
31
0
Order By: Relevance
“…The polynomial speed-up in the search process represents an advantage over the classical counterpart, O(N ). The algorithm belongs to the class of probabilistic quantum algorithms and a detailed description can be found elsewhere [9,23,[33][34][35][36]. The exposition here is restricted to the description of the two-qubit quantum circuit, which is represented in figure 3.…”
Section: (D) Grover's Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…The polynomial speed-up in the search process represents an advantage over the classical counterpart, O(N ). The algorithm belongs to the class of probabilistic quantum algorithms and a detailed description can be found elsewhere [9,23,[33][34][35][36]. The exposition here is restricted to the description of the two-qubit quantum circuit, which is represented in figure 3.…”
Section: (D) Grover's Algorithmmentioning
confidence: 99%
“…Using circularly polarized RF pulses combined with double quantum excitation, Possa et al [18] demonstrated the creation of two-qubit PPS and the implementation of the C-NOT gate in zero-field NQR of nuclei with I = 3 2 in an axially symmetric EFG, taking 35 Cl nuclei in a single crystal of KClO 3 as an illustrative example. The required pulse sequences were detailed, and the results of typical experiments were simulated using a numerical procedure.…”
Section: Nuclear Quadrupole Resonance Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…A driving Hamiltonian is then con-structed, without any knowledge of the solution, to produce a Rabi-like half-cycle which populates the marked state in a time scaling as N 1/2 , thereby exhibiting the quadratic speedup. An experimental realization of this analog Grover algorithm has been performed by NMR [11] in a setting where a quadrupolar coupling makes a spin 3/2 nucleus a two-qubit system (N =4).…”
Section: Introductionmentioning
confidence: 99%
“…Several quantum algorithms outperforming their classical analogs have been proposed and implemented more or less successfully. These algorithms, based on the quantum parallelism, target such problems like factoring large numbers into prime numbers 2 , optimization 3 , and search 4 . The incredible possibilities offered by quantum computers made the scientists invest a lot of efforts in this field.…”
mentioning
confidence: 99%